PENDIDIKAN KARAKTER TOKOH UTAMA DALAM NOVEL MERASA PINTAR, BODOH SAJA TAK PUNYA KARYA RUSDI MATHARI ( ANALISIS PSIKOLOGI SASTRA) - Charin Setya Handayani; Titik Sudiatmi; Suparmin Suparmin (STKIP PGRI Jombang, 2022)
AbstractThis research aims to describe how the character in the main character and also the structure of his personality, especially in relation to character education in the novel by Rusdi Mathari entitled